2020
DOI: 10.3389/fsurg.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Death After Thrombectomy in the Treatment of Acute Stroke

Abstract: Introduction: Treatments for acute stroke have significantly improved in the past decade, with emergent thrombectomy emerging as the standard of care. Despite these advancements, death after successful thrombectomy continues to pose a significant problem. Identifying patients least likely to benefit from thrombectomy would improve use of a limited resource and management of patient expectations. Method: We retrospectively reviewed the medical records of patients who underwent emergent thrombectomy of either an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…28 It should be noted that the majority of deaths in our study occurred in patients who were at least 80 years old and mostly with pre-existing conditions. Since it is known that octogenarians are at greater risk of mortality, 29 the safety profile of the Tigertriever 13 device may be higher in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…28 It should be noted that the majority of deaths in our study occurred in patients who were at least 80 years old and mostly with pre-existing conditions. Since it is known that octogenarians are at greater risk of mortality, 29 the safety profile of the Tigertriever 13 device may be higher in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral ischemia, stroke, subarachnoid hemorrhage (SAH), and traumatic brain injury (TBI) all produce substantial neuronal death that, if not fatal, can create lasting disabilities with significant societal impact. Few therapeutic options are currently available for stroke apart from dissolution of the vessel clot in a subset of patients (Turner et al, 2020), or clot retrieval when blockages occur in large arteries (Awad et al, 2020). SAH can be treated with Ca 2+ channel blockers (Carlson et al, 2020), however there remains considerable opportunity for improved therapies as a significant fraction of patients progress to subsequent ischemic episodes and death (Longstreth et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while good revascularization may improve survival in the thrombectomy population 24 26 , our study demonstrated that TICI 2b-3 revascularization, compared to no EVT, produced a survival benefit. This may seem intuitive, as patients receiving no EVT may be categorized into the “no revascularization” or “poor revascularization” group of a thrombectomy-only study.…”
Section: Discussionmentioning
confidence: 58%
“…Good reperfusion, defined as achieving TICI 2b-3, has been associated with improved functional outcome after LAO stroke 29 , 30 and may improve survival in the subset of LAO patients that are treated with EVT 24 26 . Our study demonstrated that compared to no EVT, good revascularization improved odds of survival.…”
Section: Discussionmentioning
confidence: 99%